2012
DOI: 10.4209/aaqr.2011.09.0156
|View full text |Cite
|
Sign up to set email alerts
|

Metal Distribution Characteristics in a Laboratory Waste Incinerator

Abstract: The metal distribution in the emissions of a laboratory waste incinerator (LWI) was investigated. The input materials and output materials (fly ash, bottom ash, and flue gas) were analyzed to examine the transportation and transmission behavior of heavy metals.Toxic (As, Cd, Cr, Hg, Ni, and Pb), anthropogenic (Ag, Ba, Cu, Mn, Se, and Zn) and crust (Na) elements were adopted to characterize the distribution properties of the LWI under investigation. The results indicated that Ba, Cr and Hg (80.0, 13.0 and 12.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Among them, absorption by sorbents provides a relatively direct and convenient way to remove the contaminants resulted from coal gasification. Popular candidates for desulfurization include Ca-based sorbent (Li et al, 2007), Fe-based sorbent (Ko et al, 2006), Mn-based sorbent (Bakker et al, 2003;Ko et al, 2005), Zn-based sorbent (Bu et al, 2008), and mixed metal oxide sorbent (Tseng et al, 2008;Lou et al, 2009;Chang et al, 2012). As for dechlorination, absorption by Ca-based sorbents has always been a prevalent choice (Yan et al, 2003;Partanen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, absorption by sorbents provides a relatively direct and convenient way to remove the contaminants resulted from coal gasification. Popular candidates for desulfurization include Ca-based sorbent (Li et al, 2007), Fe-based sorbent (Ko et al, 2006), Mn-based sorbent (Bakker et al, 2003;Ko et al, 2005), Zn-based sorbent (Bu et al, 2008), and mixed metal oxide sorbent (Tseng et al, 2008;Lou et al, 2009;Chang et al, 2012). As for dechlorination, absorption by Ca-based sorbents has always been a prevalent choice (Yan et al, 2003;Partanen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that PCDD/Fs mainly form in the temperature range of 250 to 350°C, which is the case in the first quenching towers (Hajizadeh et al, 2011;Jansson and Andersson, 2011). According to our previous study, metals which vaporized as the particulate phase reacted with Cl to form chloride in flue gas (Chang et al, 2012). During this stage, metal chloride plays an important role in catalyzing the formation of PCDD/Fs (Lu et al, 2007;Nganai et al, 2011).…”
Section: Behaviors During Incineration Processmentioning
confidence: 99%
“…The X-ray powder diffraction patterns of OMCs were measured using a D8 diffractometer (Bruker, Germany) with Ni-filtered Cu-Ka radiation between 0.6° and 6° for small-angle X-ray diffraction and between 10° and 90° for wide-angle X-ray diffraction (Chang et al, 2012;Grigoriu et al, 2012). The N 2 adsorption-desorption isotherms were measured using a ASAP2010 (Micromeritics, USA) system, and the pore size distribution curves were determined from the adsorption branch of the isotherm.…”
Section: Materials Characterizationmentioning
confidence: 99%